Apoptosis Induction by 13‐Acetoxyrolandrolide through the Mitochondrial Intrinsic Pathway. (12th December 2013) - Acuña, Ulyana Muñoz; Matthew, Susan; Pan, Li; Kinghorn, A. Douglas; Swanson, Steven M.; Carcache de Blanco, Esperanza J
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the mechanisms of cytotoxicity of the sesquiterpene lactone 13‐acetoxyrolandrolide, a nuclear factor kappa B (NF‐κB) inhibitor that was previously isolated from Rolandra fruticosa. The effects associated with the inhibition of the NF‐κB pathway included dose‐dependent inhibition of the NF‐κB subunit p65 (RelA) and inhibition of upstream mediators IKKβ and oncogenic Kirsten rat sarcoma (K‐Ras). The inhibitory concentration of 13‐acetoxyrolandrolide on K‐Ras was 7.7 µm. The downstream effects of the inhibition of NF‐κB activation were also investigated in vitro. After 24 h of treatment with 13‐acetoxyrolandrolide, the mitochondrial transmembrane potential was depolarized in human colon cancer (HT‐29) cells. The mitochondrial oxidative phosphorylation was also negatively affected, and reduced levels of nicotinamine adenine dinucleotide phosphate (NAD(P)H) were detected after 2 h of 13‐acetoxyrolandrolide exposure. Furthermore, the expression of the pro‐apoptotic protein caspase‐3 increased in a concentration‐dependent manner. Cell flow cytometry showed that 13‐acetoxyrolandrolide induced cell cycle arrest at G1, indicating that the treated cells had undergone caspase‐3‐mediated apoptosis, indicating negative effects on cancer cell proliferation. These results suggest that 13‐acetoxyrolandrolide inhibits NF‐κB and K‐Ras and promotes cell death mediated through the mitochondrial apoptotic pathway. Copyright © 2013 John Wiley & Sons, Ltd.